Subtotal petrosectomy - a tertiary center’s experience - Pedro Branco; Catarina Pimentel Morais; Joana Guincho; Tiago Colaço; Luís Castelhano; Filipe Correia; Ricardo Santos; Sílvia Pereira; Pedro Escada (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction: Subtotal Petrosectomy (SPT) is an effective and definitive solution in cases of recurrent chronic otitis media. The expansion of its indications demonstrates its usefulness and safety in resolving various challenging otologic pathologies.